Examining the Regional Co‐Variability of the Atmospheric Water and Energy Imbalances in Different Model Configurations—Linking Clouds and Circulation. (4th June 2022) - Dagan, Guy; Stier, Philip; Dingley, Beth; Williams, Andrew I. L.
Abstract: Clouds are a key player in the global climate system, affecting the atmospheric water and energy budgets, and they are strongly coupled to the large‐scale atmospheric circulation. Here, we examine the co‐variability of the atmospheric energy and water budget imbalances in three different global model configurations–radiative‐convective equilibrium, aqua‐planet, and global simulations with land. The gradual increase in the level of complexity of the model configuration enables an investigation of the effects of rotation, meridional temperature gradient, land‐sea contrast, and seasonal cycle on the co‐variability of the water and energy imbalances. We demonstrate how this co‐variability is linked to both the large‐scale tropical atmospheric circulation and to cloud properties. Hence, we propose a co‐variability‐based framework that connects cloud properties to the large‐scale tropical circulation and climate system and is directly linked to the top‐down constrains on the system—the water and energy budgets. In addition, we examine how the water and energy budget imbalances co‐variability depends on the temporal averaging scale, and explain its dependency on how stationary the circulation is in the different model configurations. Finally, we demonstrate the effect of an idealized global warming and convective aggregation on this co‐variability. Plain Language Summary: Understanding the link between clouds and the atmospheric circulation is considered as a major challenge in climate science. Both atmospheric circulation and clouds are intimately linked to Earth's water and energy budgets. We show that looking at how the residuals of these budgets depend on each other and on cloud properties can provide a new framework with which to study the properties of clouds, circulations, and their respective impacts on the climate system. In this paper, we present this framework, and demonstrate its usefulness for a range of different climate model complexities. We show examples of how the framework could be used to investigate the effects of climate change on clouds and circulation. Finally, we present an application for convective aggregation (the clustering of deep convective clouds in idealized climate models). Key Points: The co‐variability of the atmospheric water and energy imbalances is examined in 3 different model configurations We explain the connection of this co‐variability to both the large‐scale circulation and cloud properties We demonstrate how this co‐variability can be used to better understand clouds‐circulations coupling